Writing for stage and screen creating a perception shift in the audience - Kramer, Sherry (London Methuen Drama, 2023)
"Combining a step-by-step analysis of the technique of writing for stage and screen with how the mystery, poetry and emotional momentum is achieved for the audience, Sherry Kramer offers an empowering, original guide for emerging and established writers. In this structured look at the way audience members progress through a work in real time, Sherry Kramer uses plain-spoken vocabulary to help writers and artists discover how to make work that will mean more to their audiences. By using examples drawn from plays, film, and streaming series, ranging from A Streetcar Named Desire to Fleabag to Pirates of the Caribbean, this study makes its concepts accessible to a wide range of artists who work in what Kramer terms 'timebound art.' The book also features multiple exercises, developed with MFA writers in The Iowa Playwrights Workshop and The Michener Center for Writers, which provide entrance points to help artists consider and create their work. Writing for Stage and Screen revolves around the notion of the perception shift, a moment of surprise that triggers insight in the audience, prompting them to reinterpret what they've just experienced, and reflect on how the patterns of their own lives might be seen in new ways. Kramer creates ways for artists to reinterpret their chosen art form, by asking them to deconstruct and reassemble their ideas about the nature of dramatic event. She argues that nothing that happens on the stage or screen can ever matter as much as the event of meaning that happens in the audience"--Provided by publisher.
1 Works of art teach us how to read them -- 2 The perception shift -- 3 Theatre is a rhyme for life -- 4 Story and plot -- 5 Choice and consequence -- 6 In retrospect, inevitable -- 7 Convergence
Includes bibliographical references (pages 213-215) and index.
Keywords: Playwriting; Motion picture authorship; Drama -- Technique; Theater audiences; Motion picture audiences